Surface transfer in the acquisition of grammatical gender in L2 Swedish. A longitudinal study - Długosz, Kamil (Folia Scandinavica Posnaniensia, 2023)
This longitudinal study explores two specific aspects of the acquisition of grammatical gender in L2 Swedish: the use of a default gender and surface transfer. Twenty-one L1 Polish university students of L2 Swedish were tested by means of an untimed gender assignment task after two, three, and four semesters of studying. The data were analysed using a two-way ANOVA for repeated measures. Participants had more success in assigning gender to Swedish nouns that shared gender across Polish and Swedish than to Swedish nouns that differed in gender across the two languages, regardless of length of experience in learning Swedish. Contrary to previous studies that observed overgeneralisation of uter gender forms in production, this study did not identify the tendency to use uter as a default, presumably because participants had unlimited time to perform the task. This finding points to a dissociation between the knowledge of grammatical gender and the ability to use it during processing.